Deletion of classical transient receptor potential 1, 3 and 6 alters pulmonary vasoconstriction in chronic hypoxia-induced pulmonary hypertension in mice - Malkmus, Kathrin; Brosien, Monika; Knoepp, Fenja; Schaffelhofer, Lisa; Grimminger, Friedrich; Rummel, Christoph; Gudermann, Thomas; Dietrich, Alexander; Birnbaumer, Lutz; Weissmann, Norbert; Kraut, Simone (Frontiers in Physiology, 2022)
Chronic hypoxia-induced pulmonary hypertension (CHPH) is a severe disease that is characterized by increased proliferation and migration of pulmonary arterial smooth muscle cells (PASMCs) leading to pulmonary vascular remodeling. The resulting increase in pulmonary vascular resistance (PVR) causes right ventricular hypertrophy and ultimately right heart failure. In addition, increased PVR can also be a consequence of hypoxic pulmonary vasoconstriction (HPV) under generalized hypoxia. Increased proliferation and migration of PASMCs are often associated with high intracellular Ca2+ concentration. Recent publications suggest that Ca2+-permeable nonselective classical transient receptor potential (TRPC) proteins – especially TRPC1 and 6 – are crucially involved in acute and sustained hypoxic responses and the pathogenesis of CHPH. The aim of our study was to investigate whether the simultaneous deletion of TRPC proteins 1, 3 and 6 protects against CHPH-development and affects HPV in mice. We used a mouse model of chronic hypoxia as well as isolated, ventilated and perfused mouse lungs and PASMC cell cultures. Although right ventricular systolic pressure as well as echocardiographically assessed PVR and RVWT were lower in TRPC1, 3, 6-deficient mice, these changes were not related to a decreased degree of pulmonary vascular muscularization and a reduced proliferation of PASMCs. However, both acute and sustained HPV were almost absent in the TRPC1, 3, 6-deficient mice and their vasoconstrictor response upon KCl application was reduced. This was further validated by myographical experiments. Our data revealed that 1) TRPC1, 3, 6-deficient mice are partially protected against development of CHPH, 2) these changes may be caused by diminished HPV and not an altered pulmonary vascular remodeling.